2021
DOI: 10.1155/2021/8523091
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Stability of Extemporaneous Pediatric Oral Formulations

Abstract: Background. Extemporaneous compounding is a pharmacy practice to produce suitable pharmaceutical preparations when there are no commercially available, licensed, and age-specific dosage forms. Compared to the use of authorized drugs, these preparations have significant risks. Stability issues are one of the major concerns during the preparation of extemporaneous formulations. Aim. The aim of this work was to study the stability of pediatric extemporaneous formulations of commercially available conventional sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The toxicological stability can be associated with the minimum toxicity effect. The sterility or resistance toward microbial growth according to the specified requirements can be evaluated to assess the microbiological stability [ 13 , 78 , 79 , 80 ]. A previous study found that the risk of contamination was increased 100-fold in extemporaneous products compounded by nurses or other medical staff compared to those prepared by pharmacists [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The toxicological stability can be associated with the minimum toxicity effect. The sterility or resistance toward microbial growth according to the specified requirements can be evaluated to assess the microbiological stability [ 13 , 78 , 79 , 80 ]. A previous study found that the risk of contamination was increased 100-fold in extemporaneous products compounded by nurses or other medical staff compared to those prepared by pharmacists [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some extemporaneous preparations are associated with the incidence of adverse events in pediatric patients [ 12 ]. The use of licensed drugs for pediatric patients has the potential to be dangerous, because excipients are not suitable for children, even if administered in small amounts [ 13 ]. Since extemporaneous compounding is described as a branch of pharmacy practice aiming to produce appropriate pharmaceutical preparations when there are no commercially available, licensed, and age-specific dosage forms, problems related to stability, pharmacokinetic profile, and drug effect may potentially occur [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that, a linear discriminant analysis (LDA) coupled with the meta-heuristic simulated annealing (SA) variable selection algorithm [30][31][32][33] was implemented. The SA algorithm was used to identify the best sub-set of non-redundant E-tongue sensors [34] which could provide information about the capability of the selected oral formulation to mask the bitterness of the Ra-HCl and to compare it with that of the syrup. The LDA performance was checked for the original grouped data (training) as well as for the leave-one-out cross-validation (LOO-CV) procedure, graphically for the former, based on the 2D plots of the two most significant discriminant functions (DF) and based on the sensitivity values (i.e., the percentage of samples correctly classified into the pre-established groups) for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Suspensions are a liquid form of medication containing finely divided insoluble therapeutically active ingredients dispersed uniformly throughout the suspending medium (47). Suspension can be stable for 30-90 days depending on preparation (48,49). Data on suspensions are quite limited, with only a few formal studies on the palatability and stability of different suspensions reported in the literature (50,51).…”
Section: Discussionmentioning
confidence: 99%